Human DNA polymerase alpha gene: sequences controlling expression in cycling and serum-stimulated cells. - Pearson, B E (1991)
We have investigated the DNA polymerase alpha promoter sequence requirements for the expression of a heterologous gene in actively cycling cells and following serum addition to serum-deprived cells. An 11.4-kb genomic clone that spans the 5' end of this gene and includes 1.62 kb of sequence upstream from the translation start site was isolated. The transcription start site was mapped at 46 +/- 1 nucleotides upstream from the translation start site. The upstream sequence is GC rich and lacks a TATA sequence but has a CCAAT sequence on the opposite strand. Analysis of a set of deletion constructs in transient transfection assays demonstrated that efficient expression of the reporter in cycling cells requires 248 bp of sequence upstream from the cap site. Clustered within these 248 nucleotides are sequences similar to consensus sequences for Sp1-, Ap1-, Ap2-, and E2F-binding sites. The CCAAT sequence and the potential E2F- and Ap1-binding sites are shown to be protected from DNase I digestion by partially purified nuclear proteins. The DNA polymerase alpha promoter can confer upon the reporter an appropriate, late response to serum addition. No single sequence element could be shown to confer serum inducibility. Rather, multiple sequence elements appear to mediate the full serum response.